Creatine supplementation in wistar rats submitted to physical tests of swimming: evaluation of the physiological effects through raman spectroscopy - Miranda, Humberto (2011)
Creatine is a nitrogenous organic acid that naturally occurs in vertebrates. This compound is associated to energy supply to muscles, being that its biological synthesis occurs mainly in liver and is related to the aminoacids glycine, arginine and ornitine. Several studies have shown the benefits of creatine supplementation, such as higher muscle power, increased fat-free mass, and strength in healthy subjects. Besides, it can be applied as therapeutic agent for some diseases. In this work, the physical condition of Wistar rats that received creatine supplementation is compared with individuals without any supplementation. For this evaluation, swimming tests were developed in order to elucidate the physical condition of animals in different nutritional conditions. Indeed, swimming is considered one of the most complete exercises, since the practice of this physical activity involves great increase in the aerobic and anaerobic capability. Raman spectroscopy was employed to analyse the biochemical profile of the biological tissues obtained from the animals evaluated in the experiments. The present results allow to infer that the association of these two factors, i.e., the addition of creatine supplementation together with physical activity, propitiates a completely different physiological effect when compared with the isolated action of each one of these factors (creatine supplementation and physical activity). In fact, these factors seem to act in synergy, favoring a more accentuated physiological response. In fact, the data obtained in this work denotes that the physical activity, as well as the creatine supplementation, when used independently, does not provoke a very significant physiological effect. Raman spectroscopy was able to analyze important biological indicators, such as protein concentration in blood and intensity of metabolic activity, being an interesting option to similar biophysical evaluations.